Immigration in the media sphere: key political actors’ strategies (Communication & Society, 2018)
This article explores the ideological positions and communications strategies adopted by different actors who are relevant in the news coverage of immigration and immigrants. A methodological model was designed that considers the mass media as creators of discourses, and the public authorities and social organisations as promotors of policies and sources of information that can influence the media sphere. Similarly, this analytical model makes it possible to examine the interrelations that take place amongst the selected actors during the process of news production, as well as in possible spaces for dialogue and the management of joint policies. The Basque Autonomous Region was chosen as the area for the case study, with a sample that is funnel-shaped, making it possible to start out from the local level (small organisations, local journalism, major town councils) and then to obtain a broader vision of this context (immigrants’ platforms, policies managed by the Basque Government, mass media). Amongst the main conclusions, we underscore the fact that the actors interviewed agree on their diagnosis of the quality of the treatment of immigration and immigrants in the news, the difficulty of seeing migration as a phenomenon with a broad scope, the controversial role played by the media, as well as actors’ lack of systematic communications strategies that might influence the media sphere.